2007
DOI: 10.1002/jmor.10566
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and fate of the spermatozoa of Inachus phalangium (Decapoda, Majidae): Description of novel sperm structures and evidence for an additional mechanism of sperm competition in brachyura

Abstract: Various aspects of the reproductive anatomy of the spider crab Inachus phalangium are investigated utilizing light and electron microscopy. Spermatozoal ultrastructure reveals the presence of a glycocalyx in the peripheral region of the periopercular rim, never recorded before in crustacean sperm cells. Sperm cell morphological traits such as semi-lunar acrosome shape, centrally perforate and flat operculum, and absence of a thickened ring, are shared only with Macropodia longirostris, confirming a close phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
39
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 30 publications
13
39
0
Order By: Relevance
“…For example, the separation between the Gecarcinucidae and Potamidae families in the Potamoidea is confirmed by the presence of a middle acrosomal layer in the sperm of the Potamidae (represented by the subfamily Potamiscinae by Klaus et al, 2009). Similarly, the differences observed between the spermatozoa of Macropodia longirostris and Inachus phalangium (Rorandelli et al, 2008) and the rest of Majoidea, including the spider crab Maja brachydactyla, support the existence of a taxonomic unit within the Inachinae, as suggested by larval studies (see discussion of Rorandelli et al, 2008).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…For example, the separation between the Gecarcinucidae and Potamidae families in the Potamoidea is confirmed by the presence of a middle acrosomal layer in the sperm of the Potamidae (represented by the subfamily Potamiscinae by Klaus et al, 2009). Similarly, the differences observed between the spermatozoa of Macropodia longirostris and Inachus phalangium (Rorandelli et al, 2008) and the rest of Majoidea, including the spider crab Maja brachydactyla, support the existence of a taxonomic unit within the Inachinae, as suggested by larval studies (see discussion of Rorandelli et al, 2008).…”
Section: Introductionsupporting
confidence: 57%
“…Despite its malleability, the chromatin must also possess a minimum consistency to penetrate the oocyte without causing DNA breakage. In this regard, the chromatin close to the acrosome in I. phalangium is more electron dense (greater condensation according to Rorandelli et al, 2008) than the chromatin located in the nuclear periphery. In this case, the dense inner chromatin could better resist the mechanical traction exerted during the acrosomal eversion.…”
Section: Introductionmentioning
confidence: 94%
“…These setae could rub against the abdomen during copulation (Beninger et al, 1991). In the case of setae type 4 encountered in G2, they are similar to the "pyramid-like" setae of Maja (Neumann, 1996), the "cuspidate" setae of the maxillae and maxillipeds of Cherax quadricarinatus (von Martens, 1868) studied by Garm (2004), and the "tooth-like" setae of Inachus phalangium (Fabricius, 1775) studied by Rorandelli et al (2008). Since its fused-cuticle insertion, a mechanical function could be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The G2 is inserted inside G1 and acts as a hydraulic pump to push the seminal fluid through the ejaculatory duct (Beninger et al, 1991). The gonopod tip of O. trimaculatus has a single ending similar to the genera Chionoecetes studied by Beninger et al (1991), Maja studied by Neumann (1996), and Inachus studied by Rorandelli et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, obtaining the complete sequence of stages throughout spermatogenesis is a difficult task that would explain why so little information is available in brachyurans. Recent studies have revealed new features of the brachyuran spermiogenesis, such as the maturation of the spermatids in the vas deferens and seminal receptacles of the snow crab Chionoecetes opilio (Sainte-Marie and Sainte-Marie, 1999a,b) and the loss of a glycocalyx in the spermatozoa of Inachus phalangium in the seminal receptacle of the females (Rorandelli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%